Penatalaksanaan Fisioterapi Pada Osteoarthritis Lutut Dekstra Di RSUD Dr. Moewardi Surakarta Diajukan Guna Melengkapi Tugas Untuk Memenuhi Sebagian Persyaratan - KUSUMA, Amanda Danu; , Dwi Kurniawati, SST. Ft, M.Kes (2015)
Background : Osteoarthritis is damage to cartilage that followed the subcondral thickening, steophyte growth, damage to ligaments and joint capsule and common signs on the synovial inflammation in the joint that is often found to effuse. These abnormalities cause clinical symtoms include pain, joint stiffness, muscle weakness and impaired joint stability. Purpose : To find out the physiotherapy management on pain decreasing, increasing muscle strength, increasing joint movement range, and increasing functional ability of knee osteoarthritis condition. Therapy : Modalities used in this case are Infra Red (IR), Transcutaneus Electrical Nerve Stimulation (TENS),and exercise therapy using static contraction, free active movement, hold relax and resisted active movement. Result : After doing therapy in six times using IR, TENS and exercise therapy modalities : static pain of right knee T1 = 0 mm turn into T6 = 0 mm, right kness pressing pain T1 = 30 mm turn into T6 = 20 mm, right knee movement pain T1 = 45 mm turn into T6 = 30 mm, the strength of right and left fleksor muscle is still constant T1= 3+ and T6 = 4, right knee ekstensor muscle T1 = 3 turn into T6 = 4, active joint movement range (LGS) of right knee T1 = S 0-0-110 turn into T6 = S 0-0-115 and left knee passive T1 = S 0-0-115 turn into T6 = S 0-0- 125, presence of functional ability increasing. Conclusion : IR, TENS and exercise therapy can decrease pressing paind and movement, increase joint movement range, muscle strength and fungsional ability on knee osteoarthritis condition